2021
DOI: 10.1136/jitc-2020-001845
|View full text |Cite
|
Sign up to set email alerts
|

Prospective development and validation of a liquid immune profile-based signature (LIPS) to predict response of patients with recurrent/metastatic cancer to immune checkpoint inhibitors

Abstract: BackgroundThe predictive power of novel biological markers for treatment response to immune checkpoint inhibitors (ICI) is still not satisfactory for the majority of patients with cancer. One should identify valid predictive markers in the peripheral blood, as this is easily available before and during treatment. The current interim analysis of patients of the ST-ICI cohort therefore focuses on the development and validation of a liquid immune profile-based signature (LIPS) to predict response of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 56 publications
1
36
0
1
Order By: Relevance
“…Tumor-associated neutrophils have diametrically opposite effects at different molecular levels, which can be divided as anti-tumor N1 type and tumorpromoting N2 type (19)(20)(21). A prospective study with 104 patients identified a predictive immune signature (LIPS) based on the peripheral blood immunophenotype, including CD14 high monocytes, CD8 + /PD-1 + T cells, plasmacytoid dendritic cells, neutrophils, and CD3 + /CD56 + /CD16 + natural killer T cells (22). Based on LIPS, patients were categorized into low-and high-risk groups, and both PFS and OS were significantly longer for patients in the low-risk group than in the high-risk group, regardless of PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated neutrophils have diametrically opposite effects at different molecular levels, which can be divided as anti-tumor N1 type and tumorpromoting N2 type (19)(20)(21). A prospective study with 104 patients identified a predictive immune signature (LIPS) based on the peripheral blood immunophenotype, including CD14 high monocytes, CD8 + /PD-1 + T cells, plasmacytoid dendritic cells, neutrophils, and CD3 + /CD56 + /CD16 + natural killer T cells (22). Based on LIPS, patients were categorized into low-and high-risk groups, and both PFS and OS were significantly longer for patients in the low-risk group than in the high-risk group, regardless of PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify/select patients who are likely to respond positively to therapy with immune checkpoint inhibitors, research has moved specifically towards prognostic biomarkers in recent years [23]. We just recently identified a liquid immune profile-based signature to predict response of patients with recurrent/metastatic solid cancer to immune checkpoint inhibitors [24]. Furthermore, the limited response could be partly due to additional upregulation of other immune-suppressive immune checkpoint molecules on HNSCCs, as has already been demonstrated for the herpesvirus entry mediator (HVEM) in breast cancer [25].…”
Section: Introductionmentioning
confidence: 99%
“…This finding sheds new light on CD8+ T cell exhaustion, interpreting this phenomenon not only as the loss of effector activities but also as a progressive functional switch from effector to regulatory functions. The recent finding that enrichment of peripheral CD8+PD1+ T cell associates with poor overall survival in a cohort of patients affected by metastatic cancer (≈50% HNSCC) and submitted to immune-checkpoint inhibitors [ 53 ] may be interpreted as a clinical consequence of the biologic phenomena highlighted by our data.…”
Section: Discussionmentioning
confidence: 65%